Intracerebral Haemorrhage- Follow up and outcome data from Colombo South Stroke Registry - Rathypriya, B.; Pathirana, N.; Maathury, S.; Wickramasinghe, M.C.; Madanayake, P.; Gunatilake, S.B. (My University, 2016)
Attached

Intracerebral haemorrhage (ICH) has a high mortality and morbidity. Data on outcomes of ICH patients from Sri Lanka are limited. Colombo South Stroke Registry is a hospital based data bank of first ever, all strokes admitted to hospital. Objectives: To study the outcomes- mortality and morbidity patients admitted and diagnosed to have had an ICH. Methods: All ICH patients were selected from the Stroke data bank. The diagnosis was made after a positive CT scan on after admission. The relevant information were extracted from the available data. Results: Of the 694 all strokes 112 (16%) were ICHs. Of the ICH patients 33 were lost to follow up. We analyzed the data in 79 (79/112,70.54%). Males consisted of 57% and females 43%. Five were referred to neurosurgeons and only one had an intervention. There were 26 in hospital deaths attributable to the effects of the ICH. At 6 months post ICH 41 were dead (41/79,51.89%). Mean age of alive was 63 and dead was 68. All the patients who died post discharge had a MRS of 4-5 at discharge. Of the living 40,10 have a MRS of 4-5 after 6 months. Conclusions: Despite maintaining a registry, follow up of patients are not satisfactory. Mortality is about 52%. Patients are discharged from hospital to home with severe disability. Disabilities are severe in most alive patients at 6 months.